Short communication: Greater crested tern Thalasseus bergii population on the South Coast of Getem, Jember, Indonesia - Rohman, Abdu; Sara, Emman Yoga; Mujib, Muhammad Asyroful; Wibowo, Waskito Kukuh (Aceh Journal of Animal Science, 2023)
Greater crested tern (Thalasseus bergii) is a common resident seabirds in Indonesia. Habitat beach and rest on the shore with other groups of terns. This study aimed to determine the population of Greater crested tern on the southern coast of Getem Jember.Determination of observation points using a purposive sampling method. Data collection uses the encounter rates method.Bird watching in the morning from 06.00-08.00 and afternoon from 15.30-17.30. Recording data on species, number of birds, and other supporting data. Identify using relevant bird feathers. Analysis of bird species' density index data.Using monocular binoculars, camera, and global positioning system support tools. The survey of four sites revealed 413 individuals of great-crested tern. Analysis of individual density at the mouth of the river 60 individuals/Ha. It was concluded that the River mouth is the most excellent location for greater crested ternThalasseus bergii.